Investigation of Filamentous Fungi Producing Safe, Functional Water-Soluble Pigments. Issue 3 (3rd July 2018) - Heo, Young Mok; Kim, Kyeongwon; Kwon, Sun Lul; Na, Joorim; Lee, Hanbyul; Jang, Seokyoon; Kim, Chul Hwan; Jung, Jinho; Kim, Jae-Jin
Abstract: The production of water-soluble pigments by fungal strains indigenous to South Korea was investigated to find those that are highly productive in submerged culture. Among 113 candidates, 34 strains that colored the inoculated potato dextrose agar medium were selected. They were cultured in potato dextrose broth and extracted with ethanol. The productivity, functionality (radical-scavenging activities), and color information (CIELAB values) of the pigment extracts were measured. Five species produced intense yellowish pigments, and two produced intense reddish pigments that ranked the highest in terms of absorbance units produced per day. The pigment extracts of Penicillium miczynskii, Sanghuangporus baumii, Trichoderma sp. 1, and Trichoderma afroharzianum exhibited high radical-scavenging activity. However, the S. baumii extract showed moderate toxicity in the acute toxicity test, which limits the industrial application of this pigment. In conclusion, P. miczynskii KUC1721, Trichoderma sp. 1 KUC1716, and T. afroharzianum KUC21213 were the best fungal candidates to be industrial producers of safe, functional water-soluble pigments.